MODEL KEPEMIMPINAN KRISTEN YANG RELEVAN UNTUK PEMUDA DALAM KONTEKS KONTEMPORER - Imeldayanti Mangape; Meldawati Pakila'; Andrianus Pappang; Elsya Limbolele; Abijaner Abijaner (Pondok Pesantren Baitul Qur`an Sambas, 2023)
This research aims to examine and develop a relevant Christian leadership model for youth in the contemporary context. By integrating traditional Christian elements with a profound understanding of the characteristics and aspirations of the younger generation, this study explores ways in which leadership models can be adapted to respond to the challenges and needs of today's youth. The research methodology involves literature analysis and a survey among Christian youth. The findings highlight the importance of principles such as servant leadership, social justice, and empowerment in shaping a leadership model that can motivate, guide, and empower young people. The research conclusion offers an in-depth perspective on how Christian leadership models can be relevant and effective in developing impactful leadership amidst contemporary changes. The practical implications of this research contribute to the development of leadership models that meet the demands of the times and motivate Christian youth to actively engage in service and leadership in the evolving societal context.